Harmonisasi Sebagai Jalan Interspiritualitas Dalam Relasi Kristen-Islam di Toraja - Yudha Nugraha Manguju (KAMASEAN: Jurnal Teologi Kristen, 2022)
Religious practices often contribute to violence and divisions in society. This is due to self-understanding that feels the most correct and views ethnic, religious, racial, and intergroup differences (SARA) as a threat, which in the future can plunge people into religious fanaticism. This paper uses a qualitative-descriptive research method with a literature study approach to books and journals on religious life in Toraja that discuss the topic of inter-spirituality. This article shows how interreligious life now needs to be surpassed and developed into inter-spirituality as a lifestyle of religious people in the context of a plural society. Therefore, this paper aims to explore local values (local wisdom) as an effort to establish and build religious relations that integrated the concept of harmonization. Thus, the concept of harmonization can be a path of inter-spirituality that has the values of openness, equality, justice, unity, togetherness, and karapasan (peace) in building relations between religious people in Toraja. Harmony is important because it shows an attitude of living together that is cooperative, honest, open, peaceful, orderly, fair, peaceful, and holistic. Abstrak: Praktik keagamaan acap kali memberi sumbangsih terhadap kekerasan hingga perpecahan dalam masyarakat. Hal tersebut disebabkan oleh pemahaman diri yang merasa paling benar dan memandang perbedaan suku, agama, ras dan antargolongan (SARA) sebagai suatu ancaman, yang dikemudian hari dapat menjerumuskan manusia pada sikap fanatisme beragama.  Tulisan ini menggunakan metode penelitian kualitatif-deskriptif dengan pendekatan studi pustaka atas buku dan sejumlah jurnal mengenai kehidupan keberagamaan di Toraja yang membahas topik interspiritualitas. Artikel ini memperlihatkan bagaimana kehidupan interreligius kini perlu dilampaui dan dikembangkan menjadi interspiritualitas sebagai pola hidup umat beragama dalam konteks masyarakat plural. Oleh karena itu, tulisan ini bertujuan menggali nilai lokal (local wisdom) sebagai upaya untuk menjalin dan membangun relasi umat beragama yang menyatu dalam konsep harmonisasi. Dengan demikian, konsep harmonisasi dapat menjadi jalan interspiritualitas yang memiliki nilai keterbukaan, kesetaraan, keadilan, kesatuan, kebersamaan dan karapasan (kedamaian) dalam membangun relasi antarumat beragama di Toraja. Keharmonisan menjadi penting karena menunjukkan sikap hidup bersama yang bergotong royong, jujur, terbuka, tentram, tertib, adil, damai dan holistik.